The 3rd Alternative : Solving Life's Most Difficult Problems - Stephen R Covey (Simon & Schuster, 2011)
Recognized as one of Time magazine\\\'s 25 most influential Americans, Stephen R. Covey has dedicated his life to demonstrating how every person can truly control their destiny with profound, yet straightforward guidance. As an internationally respected leadership authority, familyexpert, teacher, organizational consultant and author, his advice has given insight to millions. He has sold over 20 million books sold (in 38 languages), and The 7 Habits of Highly Effective People was named the No. 1 Most Influential Business Book of the Twentieth Century. His most recent major book, The 8th Habit , has sold nearly 400,000 copies. He holds an MBA from Harvard, and doctorate degree from Brigham Young University. He is the co-founder and vice chairman of FranklinCovey, the leading global professional services firm with offices in 123 countries. He lives with his wife and family in Utah